Activation Syndrome in a Patient With Attention-Deficit/Hyperactivity Disorder Treated With Atomoxetine: A Case Report. Issue 3 (4th May 2021) - Karakaya, Sümeyra Elif Kaplan; Yektaş, Çiğdem; Tufan, Ali Evren
Abstract: "Activation syndrome" represents a cluster of symptoms of excessive emotional arousal or behavioral activation, which emerges after the first few weeks of antidepressant treatment or a dose increase and resolves with dose reduction or cessation of treatment. It was reported after treatment with selective serotonin reuptake inhibitor and serotonin-norepinephrine reuptake inhibitor group of agents, but no case of activation syndrome has been reported with the norepinephrine reuptake inhibitor group. Atomoxetine is a norepinephrine reuptake inhibitor and nonstimulant and is used to manage symptoms of attention-deficit/hyperactivity disorder (ADHD). Atomoxetine-related symptoms of mania and hypomania were reported in literature previously. Here, we report a case of activation syndrome arising after atomoxetine (ATX) dose titration in a prepubertal male child with ADHD. Differentiation of activation symptoms from mania/hypomania symptoms after treatment with ATX may be important for the clinicians to manage the adverse effects and understand the risk factors behind activation syndrome with use of ATX in children and adolescents diagnosed with ADHD.